ASKETISME DALAM AJARAN YOGA - Nerta, I Wayan (Jurnal Penjaminan Mutu, 2015)
Acceleration of science and technology enhances the positive sides of menâs life. However, as the social problems remain, peace is just needed. The HinduYoga can help people to experience spiritual freedom therefore gain peaceful life. It teaches discipline and strength to the mind, body, and soul.